# Alg 2

posted by .

By what amount does the sum of the roots exceed the product of the roots of the equation (x-7)(x+3)=0?

I have no idea what to do!

• Alg 2 -

first get the roots,,
(x-7)(x+3)=0
thus equating each term inside the parenthesis to zero,
x-7=0 and x+3=0
therefore, x=7 and x=-3
the roots are 7 and -3
sum: 7 + (-3) = 4
product: 7(-3) = -21
the questions asks for the difference between the sum and product, therefore:
4 - (-21) = 25

hope this helps~ :)

## Similar Questions

1. ### Algebra

Given the roots, 1/2 and 4, find: (A) The quadratic equation 2x^2-9x+4 ?
2. ### Alg II

I'm working with finding roots of polynomial equations with degrees of 3 or higher. I have the equation r(x)=x^4-6x^3+12x^2=6x-13 I used a graphing calculator to find the real roots of 1,-1 Then I did synthetic using -1, and I ended …
3. ### Alg II

I'm working with finding roots of polynomial equations with degrees of 3 or higher. I have the equation r(x)=x^4-6x^3+12x^2=6x-13 I used a graphing calculator to find the real roots of 1,-1 Then I did synthetic using -1, and I ended …
4. ### math

If the sum of the roots of 2 x squared - 6 x + 7 equals zero is multiplied by the product of its roots the result is
5. ### Math

The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots such that the squares of the roots are the same as the two roots. Calculate the product pq.
6. ### Algebra

The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots such that the squares of the roots are the same as the two roots. Calculate the product pq. I think the obvious root would be one but the second roots i just can't …